2004
DOI: 10.1007/s00395-004-0483-6
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 27 protects the heart against myocardial infarction

Abstract: Heat shock proteins (hsp) represent a group of chaperones which protects the cells against a diversity of stresses. It has been demonstrated that hsp27 is constitutively present in cells where it plays an important role in different cytoprotective processes which ultimately inhibit cell death. We investigated the response of the isolated perfused mouse heart over expressing hsp27 to the ischaemia/reperfusion injury using infarct size as an end point. Our results show for the first time that mice over expressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(75 citation statements)
references
References 14 publications
2
67
0
6
Order By: Relevance
“…Most of the current knowledge has come from animal models or limited studies on adult cardiac disease. HSP 27 expression has been shown to protect against myocardial infarction (Willis and Patterson 2010;Efthymiou et al 2004) and is increased in the rat left ventricle myocardium after coronary ligation and in human patients with dilated cardiomyopathy (Knowlton et al 1998). Studies on HSP 27 knockout mice have shown that, at least in this species, HSP 27 is not essential for cardiac development but plays a role in the antioxidative response during ischemia-reperfusion injury (Willis and Patterson 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the current knowledge has come from animal models or limited studies on adult cardiac disease. HSP 27 expression has been shown to protect against myocardial infarction (Willis and Patterson 2010;Efthymiou et al 2004) and is increased in the rat left ventricle myocardium after coronary ligation and in human patients with dilated cardiomyopathy (Knowlton et al 1998). Studies on HSP 27 knockout mice have shown that, at least in this species, HSP 27 is not essential for cardiac development but plays a role in the antioxidative response during ischemia-reperfusion injury (Willis and Patterson 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although studied in other fields of medicine, the role of HSPs before, and following paediatric cardiac surgery, is not understood. However, it is becoming clear from adult human and animal studies that HSPs may have an important role in protecting the damaged heart, which accumulates misfolded proteins (Schmitt et al 2002;Taggart et al 1997;Jayakumar et al 2000;Hollander et al 2004;Yet et al 2001;Aloy et al 2008;Franklin et al 2005;Efthymiou et al 2004 andKnowlton et al 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced Hsp70 expression level induces more infarction volume of focal cerebral ischemia in knockout mice of hsp70.1 (gene encoding inducible Hsp70) (Lee et al, 2001(Lee et al, , 2004. Overexpression of Hsp27 and aB-crystallin (HspB5) in transgenic mice showed a reduced amount of infarction (Ray et al, 2001;Efthymiou et al, 2004) and attenuated cardiomyocyte apoptosis (Ray et al, 2001). In the heart of double knockout mice of aB-crystallin and HspB2, which have shared regulatory elements in the promoter region, ischemia-reperfusion exhibits contractile dysfunction and increased myocardial infarction ( Figure 1 Proposed pathway in amyloid assembly and actions of molecular chaperones.…”
Section: Molecular Chaperones As Regulators Of Cell Death a Hishiya Amentioning
confidence: 99%
“…A second important cardioprotective element, common to PreC and PostC, is represented by chaperone proteins, also known as HSPs [12,18,41,63]. We have previously identified melusin as a new musclespecific chaperone protein binding to the cytoplasmic domain of β1 integrin and acting as mechanical stretch sensor of the cytoskeleton [8].…”
Section: Introductionmentioning
confidence: 99%